The situation in Afghanistan and its possible evolution in the context of the "factor 2014" - A. A. Orlov (Vestnik MGIMO-Universiteta)
In the article provides an analysis of the situation in Afghanistan in advance of the withdrawal of the International Security Assistance Force (ISAF) from the country and contains a forecast of possible developments in the next period. The author considers that critical importance for the future of Afghanistan has its integration into the world economy.